A The Influnence of Transformational Leadership, Work Motivation and Workload on the Performance of Employees of the Boyolali Regency Regional Secretariat - Joko Tri Winarno, Joko Tri winarno; Rini Handayani (Yayasan Multidimensi Kreatif, 2025)
This research is designed to understand the relationship between transformational leadership, work motivation, work discipline, and how these three impact employee performance within the Boyolali Regency Regional Secretariat. This research is classified as quantitative research, this is because all stages, starting from proposal formulation, research process, hypothesis formulation, data collection in the field, data analysis, drawing conclusions, to report writing involve measurement, careful calculation, and application of relevant formulas, to produce precise data. A total of 125 employees at the Boyolali Regency Regional Secretariat were a sample taken in this study. It was analyzed using a census approach to collect data, which was then by conducting a test of the validity, reliability, and normality of the questionnaire. Furthermore, the research data was analyzed using the Validity Test, Reliability Test, and Simple Linear Regression, with the help of SPSS 26 software. Primary data collection was carried out directly using questionnaires as instruments. The study concluded that employee performance is positively and significantly influenced by each of the factors of transformational leadership, work motivation, and workload.